ANALISIS FAKTOR PENDORONG PERNIKAHAN USIA MUDA DI DESA RASAU JAYA DUA KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Suci Rahayu; Rustiyarso Rustiyarso; Riama Al Hidayah (Universitas Tanjungpura, 2021)
AbstractThe purpose of this study is to know the factor behind the youth marriage in the rasau jaya village of the two core dedistrict rasau jaya district. The study USES a qualitative approach with a descriptive qualitative method. The data-collection technique used is observation, documenting interviews with data collection tools of observation guide, interview guide, and documentation. The results of this study prove that (1) knowledge was a factor in young age of marriage in the rasau jaya village of the two critical growth districts because of lack of knowledge and lack of experience. (2) the cultural factor behind a young age of marriage in the rasau jaya village of two adult subdistrict rasau jaya because of the lack of marketers and therefore motivates both youth and parents to get their children married as quickly as possible. (3) peers factor in youth marriage in the rasau jaya village of the two core district rasau jaya because of the negative influence of peers can be bad enough to trigger a youth marriage.Keywords: Driving Factor, Marriage At A Young Age